Solving a nurse scheduling problem at a 24 hour clinic using integer linear programming / Nor Adilah Towhid ... [et al.] - Towhid, Nor Adilah; Azman, Nurul Parhana; Ahmad Sanip, Nur Syazni Athirah; Ghazali, Nurdia Azlin (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Nurse scheduling problem (NSP) is important in assigning every nurse at a specitic place and appropriate times. It is a complex exercise with multiple and contradictory objectives minimizing total costs while maximizing the nurses' preterences and requests, and equally distributing workload between nurses. Constraints in nurse scheduling relate to requirements for each shift that can be assigned to each particular nurse, maximum number of consecutive days of work, minimum amount of resttime between two shifts, and isolated days of work or days-off. The time and effort were utilized efficiently in orderto balance the workload to lead to more contented and effective nurses (Kumar et al., 2014). El Adoly (2018), studied the scheduling process of nurses in a hospital in Egypt and found that the proposed model decreases overall overtime cost by 36%. This study focused at creating an optimum nurse schedule that minimize cost and employs the integer linear programming model for solving nurse scheduling problems. This study applied primary data which was collected from a selected 24*hours clinic in Seremban, Negeri Sembilan.